An Analysis on Students’ Pronunciation in Delivering a Speech - Fatmawaty Alimuddin (Lingedu: Journal of Linguistics and Education, 2025)
English pronunciation is often a challenge for Indonesian students because many English sounds are not found in Indonesian. As a result, students often mispronounce certain words when speaking English. This study aimed to analyze the English vowel pronunciation produced by third-semester students of the English Department at Muhammadiyah University of Makassar when delivering speeches. This study employed a descriptive analysis approach. Data were collected through a pronunciation test, in which students were asked to read a prepared speech script, then their reading was recorded for analysis.The data were processed through three stages: identifying pronunciation errors, grouping error types, and evaluating the frequency of each vowel pronunciation error.The results of the study showed that students made 120 pronunciation errors from the 16 words tested. The most frequent vowel sounds pronounced incorrectly were found in the words Important (12.5%), Also (11.6%), Enough (10%), Another (9.16%) and Family (8.33%) - In and Read were pronounced correctly by all students. In conclusion, students still encounter difficulties pronouncing English vowels due to their L1.This study is useful to the teaching of English pronunciation by identifying vowel sounds that may need more direct attention and learning for learning English in Indonesia.